Taxanes in the elderly patient with metastatic breast cancer [Corrigendum] - Yardley DA (Dove Medical Press, 2019)
Yardley DA. Breast Cancer Targets Therapy. 2015:7;293–301.On page 300, Disclosure section, “The author reports no conflicts of interest in the work” has been updated since publication and should read “Dr Yardley reports nonfinancial support from Celgene pertaining to the work submitted. Dr Yardley reports grants to her institution, Sarah Cannon Research Institute, for studies on which she served as Principal Investigator, outside of the submitted work, from the following companies: Novartis, Janssen, Roche/Genentech, Bristol-Myers Squibb, Amgen, Celgene, Eli Lilly, GlaxoSmithKline, Medimmune, Medivation, Pfizer, Sanofi, Tesaro, Eisai, AbbVie, Astellas, Biomarin, Celldex, Clovis, Incyte, Merrimack, Imclone, Luitpold, Macrogenics, and Veridex. Dr Yardley reports that consulting fees were paid to her institution by the following companies for Dr Yardley’s services: Novartis, Roche/Genentech, Celgene, Lilly, Pfizer, Abraxis, Eisai, Spectrum, bioTheranostics, Celldex and OncoPlex Diagnostics. Dr Yardley reports non-financial support to her institution from Astellas, Sanofi, Lilly, and Celgene. The author reports no other conflicts of interest in this work”.Read the original article.